Effects of acutely intermittent hypoxic exposure on running economy and physical performance in basketball players - Kilding, A. E.; Dobson, B. P.; Ikeda, E. (The Journal of Strength and Conditioning Research, 2016)
The aim of this study was to determine the effect of short duration intermittent hypoxic exposure (IHE) on physical performance in basketball players. Using a single-blind placebo-controlled group design, 14 trained basketball players were subjected to 15 days of passive short duration IHE (n = 7), or normoxic control (CON, n = 7), using a biofeedback nitrogen dilution device. A range of physiological, performance, and hematological variables were measured at baseline, and 10 days after IHE. After intervention, the IHE group, relative to the CON group, exhibited improvements in the Yo-Yo intermittent recovery level 1 (+4.8 ± 1.6%; effect size [ES]: 1.0 ± 0.4) and repeated high-intensity exercise test performance (-3.5 ± 1.6%; ES: -0.4 ± 0.2). Changes in hematological parameters were minimal, although soluble transferrin receptor increased after IHE (+9.2 ± 10.1%; ES: 0.3 ± 0.3). Running economy at 11 km/h (-9.0 ± 9.7%; ES: -0.7 ± 0.7) and 13 km/h was improved (-8.2 ± 6.9%; ES: -0.7 ± 0.5), but changes to VO2peak, HRpeak, and lactate were unclear. In summary, acutely IHE resulted in worthwhile changes in physical performance tests among competitive basketball players. However, physiological measures explaining the performance enhancement were in most part unclear.